Communication strategies and rural dwellers attitude towards Covid-19s’ preventive measures in Osun state, Nigeria (2020)
The study examined the influence of communication strategies on rural dwellers’ knowledge and attitude towards Covid -19s’ preventive measures. Three specific research objectives and questions were achieved and answered. Exploratory research design was employed, ten villages were purposively sampled and one-hundred (100) participants were selected with the aid of simple random sampling technique. In addition, self-developed questionnaire was used to obtain relevant information from the respondents and this was analyzed through descriptive statistical tools. The empirical findings revealed that print and broadcast media most especially radio, newspaper and television were some of the available and accessible communication strategies through which information pertaining to the Covid -19s’ preventive measures were obtained by the rural dwellers. It was discovered that rural dwellers’ attitude towards avoidance of social gathering and temporary suspension of religious activities as parts of Covid -19s’ preventive measures were encouraging to a very high extent. Besides, there was no significant difference based on gender traits and age range in the rural dwellers attitude towards Covid -19s’ preventive measures, while a significant difference was empirically established among respondents’ attitude on the basis of religious affiliations which was in favour of those with Traditional religious practice. Recommendations made included dissemination of vital information through door-to-door campaigns by the approved serving health workers and provision of required facilities such as pipe-borne water and borehole to ensure rural dwellers’ access to running water, hand sanitizers, face-mask amongst others